Potensi dan Prospek Industri Kecil - Dedi Walujadi (Bina Nusantara University, 2006)
The manufacturing sector has retained its importance in the Indonesian Economy. Since 1990 it has surpassed the agricultural sector as the main contributor to the Gross Domestic Product (GDP). Article analyses strenght and weaknesses of the small-scale manufacturing industries (SSIs). By ussing the economic contribution approach and the framework proposed by Pyke, based on 2003 data provided by BPS statistics Indonesiathe study investigates the SSIs performance in relation to their economic contribution, the collective efficiency, constant innovation and economic ofscope strategy. It is conluded that Pyke’s framework was not apply since SSIs facing lack of social infrastructures and knowledge, and mostly less educated compared with the larger one. The empirical evidence also shows that in terms of value added and labor absorption, its share less than 1 % and 16 % respectively of the whole of industrialsectors.